Innovativeness of Modern Time Education in the Context of Technological Changes - Brytan Yurii A.; Baniev Yevhen F.; Rudas Serhii V.; Vorobyov Anton M.; Slastianykova Veronika I. (Bìznes Inform, 2025)
The article explores the impact of innovativeness of modern time education on the socially responsible development of enterprises within the framework of technology transfer systems. The authors emphasize that the implementation of advanced educational methodologies, such as interactive platforms, adaptive technologies, and gamification, plays a key role in ensuring effective learning. Such approaches not only enhance student motivation but also promote their active participation in forming competencies tailored to the demands of the modern labor market. The article particularly underscores the need to address the gap between academic knowledge and practical skills by integrating real business cases, internships, and simulation training into educational programs. This creates conditions for the training of qualified specialists capable of efficiently addressing the tasks of innovative activities in the manufacturing sector. The innovativeness of modern education in the technology transfer system is a key element of socially responsible business development. The use of cutting-edge technologies and innovative approaches in educational programs contributes not only to improving the qualifications of personnel but also ensures the effective implementation of advanced technologies in enterprises. In this context, education plays an important role as a catalyst for the development of innovative processes, which in turn ensures the competitiveness and sustainability of business in the current economic environment. In modern conditions of rapid technological development and globalization of the labor market, there is a growing need for the preparation of competent professionals who have practical skills and can quickly adapt to the demands of employers. Internship programs for students, developed in collaboration with companies, can serve as an effective solution to this problem, creating mutually beneficial conditions for both educational institutions and businesses. The innovativeness of education in the context of technology transfer is an important factor that provides not only economic benefits for companies but also positively affects the social and environmental aspects of their activities.